The Broken Promise of Eco-Cities: A Socio-Legal Analysis of Institutional Decoupling in Indonesian Real Estate Projects - Ahoen, Bahori (Riviera Publishing, 2026)
While global regulatory scrutiny of greenwashing has intensified in the energy sector, the real estate industry in emerging markets remains a critical “blind spot.” This study investigates the systemic phenomenon of Institutional Decoupling in Indonesia, where property developers aggressively signal environmental virtues (Eco?Cities) to justify premium pricing, yet legally sever these promises from contractual obligations. Adopting a socio?legal multi?case study approach, this research analyzes three high?profile conflicts: Meikarta (Visionary Decoupling), Sentul City (Operational Decoupling), and the Pluit Commercial Area (Functional Decoupling). The findings reveal a Legal–Marketing Gap, in which developers exploit standard contracts (Perjanjian Baku) and exoneration clauses to render marketing signals non?binding. The study argues that without legal enforceability, green branding becomes a predatory mechanism that transfers business risk to consumers. The paper concludes by proposing a Binding Green Clause framework, recommending that environmental amenities be elevated from marketing illustrations to material contractual terms to restore trust and strategic legitimacy in the sector.